English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

show working please

2006-11-05 15:50:24 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

n/n is just 1. so this should be (1-2)-2/3=2/n-2 which would make n=6, unless you are using some strange notation that I have never seen.
(1-2)-2/3=2/n-2
-2-2/3=2/n-2
-5/3=2/n-2
add 2 to both sides
1/3=2/n
invert both sides
3/1=n/2
multiply both sides by 2
6=n

2006-11-05 16:43:10 · answer #1 · answered by Anonymous · 0 0

taking lcm of denominators,

(3n-(2(n-2)))/3(n-2) = 2/n-2

n+4/3(n-2)=2/n-2

Cancellinf n-2 on both sides.

n+4/3 = 2

cross multiplying,

n+4=6

n=2

but n=2 makes denominator of first term to be zero.

its not possible.it does nt have solution

2006-11-05 23:55:41 · answer #2 · answered by aravind 3 · 0 0

(n/n-2)-2/3=2/n-2 multiply by n-2
n-(2/3)(n-2)=2 multiply by 3
3n-2n+4=6
n=2

not valid since we are now dividing by zero

could rearange to
(n-2)/(n-2)-2/3=0
1-2/3=0
there is no solution.

2006-11-05 23:55:26 · answer #3 · answered by yupchagee 7 · 0 0

fedest.com, questions and answers